Phase structure of linear sigma model with neutrality constraint (II) - Phat, Tran Huu; Thu, Nguyen Van (Communications in Physics, 2012)
The phase structure of the linear sigma model with constituent quarks and the electric neutrality is systematically studied in the mean field theory. It results that in the chiral limit, as function of T and chemical potential (μ ), the pion condensate undergoes a first-order phase transition. In the physical world, the phase diagram of chiral condensate exhibits a first-order phase transition, which ends at a critical end point (CEP) for α < 0.3, where α is the fraction of π^+ contribution to the condensate.